Design and development of lamp of adjustable spectrum - Mazikowski, Adam; Feldzensztajn, Mateusz (Photonics Letters of Poland, 2022)
Nowadays artificial light is used in many areas of human life. Dedicated lighting allows to emphasize selected features of technical and biological objects, stimulates the growth of plants or enhances the attractiveness of products or artistic works. In this paper a developed low-cost lamp with an adjustable spectrum was presented. As light sources, several LEDs of both narrow-band and wide-band spectrum were selected. A multi-channel Raspberry PI was applied for LEDs driving and ensuring the user’s interface. To properly mix light from several different LEDs, a dedicated integration sphere was used, covered with paint based on barium sulfate. Full Text: PDF References D.L. DiLaura, K.W. Houser, R.G. Mistrick, G.R. Steffy, The lighting handbook (Illuminating Engineering Society 2011). DirectLink CREE Inc, Cree® 2835 LEDs Product family datasheet, (accessed 19 February 2022). DirectLink F. Szabó, R. Kéri, J. Schanda, P. Csuti, E/ Mihálykó-Orbán, A study of preferred colour rendering of light sources: home lighting, Lighting Research and Technology (Epub ahead of print 2014). CrossRef M. Feldzensztajn, P. Wierzba, A. Mazikowski, "Examination of Spectral Properties of Medicinal Plant Leaves Grown in Different Lighting Conditions Based on Mint Cultivation", Sensors 21, 4122 (2021), CrossRef S. Barbut, "Effect of illumination source on the appearance of fresh meat cuts", Meat Science 59(2), 187 (2001), CrossRef A.J. Knulst, R. Mooijweer, F.W. Jansen, L.P. Stassen, J. Dankelman, "Indicating shortcomings in surgical lighting systems", Minim. Invasive Theor. Apllied Technol. 20(5), 267 (2011). CrossRef C.M. Browning, M. Parker, T.C. Rich, S.J. Leavesley, "Illuminating the optical properties of an LED-based spectral light source for hyperspectral endoscopy", Proc. SPIE 11636, 1163608 (2021) CrossRef H.C. Wang, Y.T. Chen, J.T. Lin, C.P. Chiang, F.H. Cheng, "Enhanced visualization of oral cavity for early inflamed tissue detection", Opt. Expr. 18 (11), 11800 (2010). CrossRef D.H. Larsen, E.J. Woltering, C.C.S. Nicole, L.M.F. Marcelis, "Response of Basil Growth and Morphology to Light Intensity and Spectrum in a Vertical Farm", Frontiers in Plant Science 11, 597906 (2020) CrossRef T. Cegielski, D. Bujalski, K. Kowalczyk, J. Gajc-Wolska, L. Hemka, Proc. Electrotechn. Inst. 63 (273), 79 (2016), CrossRef A. Mazikowski, M. Feldzensztajn, Proc. SPIE 10445, 10445OK (2017). CrossRef A. Llenas, J. Carreras, "Arbitrary spectral matching using multi-LED lighting systems", Opt. Eng. 58(3), 035105 (2019). CrossRef F.J. Burgos et al., "Image and Signal Processing", Lect. Notes Comput. Sci. 8509, 115 (2014), CrossRef M. Feldzensztajn, A. Mazikowski, "Comparison of modelling and measurement results of spectra emitted by a programmable lamp", Photon. Lett. Poland 10(2), 42 (2018), CrossRef CIE, Publication No. 127, Measurement of LEDs (Central Bureau of the CIE, Vienna, Austria, 2007). DirectLink N. Kington, B. Bugbee, A Mixture of Barilium Sulfateand White Paint is a Low-Cost Substitute Reflectance Standard for Spectralon (Utah State University, 2005), DirectLink